RESPONS FISIOLOGIS DAN HASIL SORGUM (Sorghum bicolor L) VARIETAS LOKAL WATAR HAMMU MITING TADDA TERHADAP BERBAGAI VARIASI DOSIS NITROGEN - Arnol Tamo Ama; Suprihati (Fakultas Pertanian Universitas Janabadra, 2025)
Sorghum (Sorghum bicolor L) is one type of cereal plant that is a local and national food because it is resistant to disease and can be cultivated on marginal land. The local variety Watar Hammu Miting Tadda comes from East Sumba and has the potential to be developed in the highlands such as Kopeng, Central Java, which has different climate and soil characteristics. This study aims to determine the response of local sorghum Watar Hammu Miting Tadda to nitrogen (N) fertilizer. The study used an experimental method with a Randomized Block Design (RAK), five N fertilizer dose treatments (control; 2.44; 3.69; 4.89; and 6.08 g/plant), and four groups. The parameters observed included plant height, number of leaves, stem diameter, dry stalk weight, panicle length, seed weight per plant, tiled seed weight, and 100 seed weight. The results of the analysis showed that the N fertilizer dose treatment had a very significant effect on plant height at the age of 6 MST, with the highest height obtained at a dose of 6.08 g/plant (104.49 cm). However, the treatment did not significantly affect other parameters, such as seed weight and panicle length. The highest seed weight was recorded at a dose of 3.69 g/plant (302.38 g). This indicates that plant vegetative growth is more responsive to N fertilizer than harvest yields. These results also demonstrate the importance of site-specific nutrient management and the use of adaptive varieties to optimize yields.